Using Blockchain to Enable Cleaner, Modern Energy Systems in Emerging Markets - Miller, Douglas (International Finance Corporation, Washington, DC, 2019)
Emerging markets must attract significant international financing to meet their goals for mitigating carbon pollution and increasing access to clean, affordable, reliable, and resilient energy. The authors* of this note examine how blockchain technology can—if paired with smart, interconnected devices—promote needed investments by both improving investment processes and promoting the adoption of modern energy systems and business models. Given the nascent status of both blockchain technology and blockchain applications specific to the energy sector, this note offers guidance to better assess where and how to apply blockchain technology to achieve a modern, clean, energy future including in emerging markets.